STRATEGI KOMUNIKASI KOMUNITAS GUBUAK KOPI DALAM MELESTARIKAN BUDAYA MASYARAKAT PERTANIAN DI KOTA SOLOK - Irvan, Mohammad; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this research is to know the communication strategy of Community Gubuak Kopi in preserving the culture of agricultural communities in Solok City. This research uses qualitative descriptive research methods. Data collection techniques used in this research are interviews, observations, and documentation. The subjects involved in this study was determined based on technique purposive, comprising the chairman of the Community Gubuak Kopi, secretary of community Gubuak Kopi, Treasurer Community Gubuak Coffee, and the board of production in the Community Gubuak coffee. Technical analysis of data conducted using data analysis Model Miles (1994) and Faisal (2003) Using Data validity inspection technique is the extension of participation and triangulation of the source.Community of Gubuak Kopi is a non-profit group culture studies based on research and development of art and media knowledge in Solok City, West Sumatera province. Community of Gubuak Kopi has a purpose to produce and distribute knowledge of media literacy through creative activities, organizing, and between professionals (artists, writers, and researchers) and citizens in participatory. In addition, community Gubuak Kopi also developed local media and filing systems, as well as establishing an alternative space for the development of cultural awareness in Solok City, and West Sumatra province in general.The results of the research show that community Gubuak Kopi uses communication strategy with strategic communication model, that is through a communicators strategy, where the community Gubuak Kopi in conveying information consists of a young generation who has knowledge of how media art works or understands about artistry that is a method of not product end results. The message is about preserving the culture of agricultural communities that are around the community, the importance of media literacy in the midst of society, and the use of media for cultural activities and in archiving culture Own. Furthermore, the methods used in conveying information are by repetition methods (repetition), into, and educative. The media used is through printed media (books, journals and comics), electronic media (online media) such as websites, social media and digital media YouTube, and also media groups such as workshop activities and exhibitions. Community target Audience Gubuak Kopi is a local community in the city of Solok as a primary audience and public/wide as a secondary audience. Keyword: Culture, Preserving, Gubuak Kopi Community, Strategy of Communication